2011
DOI: 10.1021/bi101722b
|View full text |Cite
|
Sign up to set email alerts
|

Topological Probes of Monoamine Oxidases A and B in Rat Liver Mitochondria: Inhibition by TEMPO-Substituted Pargyline Analogues and Inactivation by Proteolysis

Abstract: TEMPO-substituted pargyline analogues differentially inhibit recombinant human Monoamine Oxidase A (MAO A) and B (MAO B) in intact yeast mitochondria suggesting these membranebound enzymes are located on differing faces of the mitochondrial outer membrane (Upadhyay, A. and Edmondson, D.E., Biochemistry 48, 3928, 2009). This approach is extended to the recombinant rat enzymes and to rat liver mitochondria. The differential specificities exhibited for human MAO A and MAO B by the meta-and para-amido TEMPO pargy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
2
9
0
2
Order By: Relevance
“…At present, we speculate that a putative GGOH-binding protein may sequester the substrate for an enzyme located in the proteinase K-resistant mitochondrial compartment. Finally, we tested GGOH oxidase activity of MAO-B because: 1) farnesol, one-unit shorter isoprenol, has been identified as a selective inhibitor for MAO-B in tobacco smoke (9) and 2) MAO-B is localized to the inner side of the mitochondrial outer membrane and is known to be proteinase K-resistant (24,27). The present data met our expectations (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…At present, we speculate that a putative GGOH-binding protein may sequester the substrate for an enzyme located in the proteinase K-resistant mitochondrial compartment. Finally, we tested GGOH oxidase activity of MAO-B because: 1) farnesol, one-unit shorter isoprenol, has been identified as a selective inhibitor for MAO-B in tobacco smoke (9) and 2) MAO-B is localized to the inner side of the mitochondrial outer membrane and is known to be proteinase K-resistant (24,27). The present data met our expectations (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, transfection-enforced overexpression of MAO-B in SH-SY5Y cells does not affect the binding to mitochondria and cytotoxicity of NM(R)Sal, even though MAO activity increases to be about 7-folds. The selective binding of NM(R)Sal to MAO-A, but not to MAO-B, might be due to the mitochondrial localization of MAO-A and MAO-B at the cytosolic, or intermembrane space of mitochondrial membrane, respectively [68]. These results clearly demonstrate that MAO-A is a target of the endogenous neurotoxin to activate apoptotic cascade.…”
Section: Mao-a Is Associated With Activation Of Death Signal Pathwaymentioning
confidence: 68%
“…In fact, more recent studies found MAO only in the outer mitochondrial membrane [60]. Interestingly, the use of TEMPO-substituted pargyline analogues (TEMPO or 2,2,6,6-tetramethyl-1-piperidinyloxy is a commonly used structure for making stable spin labels) and MAO inactivation by proteolysis allowed demonstrating that MAO-A and MAO-B are differently oriented in the outer mitochondrial membrane [64]. This finding might be of particular interest for designing novel subtype selective MAO inhibitors.…”
Section: Mao: Structure Localization and Functionmentioning
confidence: 99%